Mapping Queer Space(s) of Praxis and Pedagogy (Queer Studies and Education, 2018)
This book explores intersections of theory and practice to engage queer theory and education as it happens both in and beyond the university. Furthering work on queer pedagogy, this volume brings together educators and activists who explore how we see, write, read, experience, and, especially, teach through the fluid space of queerness. The editors and contributors are interested in how queer-identified and -influenced people create ideas, works, classrooms, and other spaces that vivify relational and (eco)systems thinking, thus challenging accepted hierarchies, binaries, and hegemonies that have long dominated pedagogy and praxis.